2009
DOI: 10.2174/138161209788682244
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Peptide Motifs Against HIV-1 Reverse Transcriptase and Integrase

Abstract: Multiple clinical benefits have been obtained thanks to the combination of drugs targeting several steps of the HIV-1 replication. However, despite such combination therapy, complete eradication of the virus cannot be attained. Moreover, emergence of resistance observed under treatment and the lengthening life expectancy of treated patients highlight the need for new anti-HIV agents. Peptide-based compounds that exhibit anti RT and anti integrase activities were particularly described. Active peptides have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 76 publications
(94 reference statements)
0
9
0
1
Order By: Relevance
“…Clinical trials with S-1360 and L-870,810 were terminated in phase I/II and II due to limited efficacy and toxicity, respectively [34,35]. Peptides and nucleic acid inhibitors of IN in vitro have also been identified by screening (phage display, yeast 2-hybrids, SELEX) or rational design (derived from viral or cellular co-factors) [39,40]. Zintevir (AR177) (Aronex Pharmaceuticals) is a G-quadraduplex-forming oligonucleotide inhibitor of both recombinant IN and HIV-1 replication at low nanomolar concentration [41,42].…”
Section: Integrase Inhibitors: Historical Overviewmentioning
confidence: 99%
“…Clinical trials with S-1360 and L-870,810 were terminated in phase I/II and II due to limited efficacy and toxicity, respectively [34,35]. Peptides and nucleic acid inhibitors of IN in vitro have also been identified by screening (phage display, yeast 2-hybrids, SELEX) or rational design (derived from viral or cellular co-factors) [39,40]. Zintevir (AR177) (Aronex Pharmaceuticals) is a G-quadraduplex-forming oligonucleotide inhibitor of both recombinant IN and HIV-1 replication at low nanomolar concentration [41,42].…”
Section: Integrase Inhibitors: Historical Overviewmentioning
confidence: 99%
“…In infected cells, RT employs tRNA 3 Lys and the polypurine tract as primers and converts the viral genomic RNA into doublestranded viral DNA (23). This process is catalyzed by both the DNA polymerase and RNase H activities of RT (23,49).…”
mentioning
confidence: 99%
“…A number of studies have elucidated the mechanisms underlying the inhibition effect of A3G on reverse transcription. It has been shown that A3G is able to interfere with multiple steps of reverse transcription, including the inhibition of tRNA 3 Lys primer annealing through an interaction with NCp7 (18)(19)(20), the blocking of strand transfers, which consequently reduces late viral DNA synthesis (34,40), and the suppression of tRNA 3 Lys cleavage and removal, which produces aberrant viral 3= long terminal repeat (LTR) ends (40). Moreover, using purified catalytically active A3G protein, it was shown that all reverse transcriptase (RT)-catalyzed DNA elongation reactions were significantly inhibited by A3G (26).…”
mentioning
confidence: 99%
“…The findings from this study suggest that the dimeric architecture of the HYB domain is necessary to engage the Tyr(P) ligand, which is in sharp contrast to all the other known Tyr(P)-binding domains that predominantly function as monomers. Selectively targeting the dimeric interface of therapeutically important enzymes has emerged as an attractive method of allosteric inhibition (62)(63)(64)(65). The importance of the dimeric architecture of HYB in Tyr(P) substrate binding demonstrated by the present study makes it an ideal target for the design of selective allosteric inhibitors that abrogate HYB dimerization and potentially act as novel therapeutic interventions against cancer.…”
Section: Discussionmentioning
confidence: 85%